Ethnobotanical knowledge of wetlands dependent communities of Koshi Tappu Wildlife Reserve, Nepal - Ghimire, Narayan Prasad; GC, Sandip; Joshi, Khagendra; Siwakoti, Mohan; Kunwar, Ripu M.; Rai, Sanjeev Kumar (Ethnobotany Research and Applications, 2025)
Background: This study documents the ethnobotanical knowledge of wetlands dependent ethnic communities (Bantar/Sardar, Mallaha, Musahar, Rajput, and Tharu) residing in the buffer zones of the Koshi Tappu Wildlife Reserve (KTWR) which includes sections of the Sapta Koshi River and its floodplains. Despite KTWR’s ecological importance, systematic research on traditional plant use remains limited. This work addresses that gap by capturing community-based knowledge on plant resource utilization. Methods: Fieldwork (April to May 2024) employed participatory methods, including semi-structured interviews, key informant surveys, and focus group discussions with 105 respondents who were residents at the buffer zone of KTWR and obtained information was interpreted using Use Value (UV) and Fidelity (FL). Plant specimens were collected and identified using reference materials, herbarium samples from the National Herbarium and Plant Laboratories (KATH) and Tribhuvan University Central Herbarium (TUCH), and experts’ consultation. Results: A total of 101 vascular plant species were documented, utilized by ethnic groups for medicinal, timber, fodder, edible, ethno-veterinary, religious/ritual, utensils and handicrafts. They utilized more plant species to in traditional healthcare systems (herbal remedies and traditional healing practices, while a smaller number of species were utilized for ethnoveterinary and other purposes. Aegle marmelos, Mangifera indica, Bombax ceiba, Cynodon dactylon, Dalbergia sissoo, and Shorea robusta were significantly valued for communities. Conclusions: The findings support the preservation of the traditional ecological knowledge vital for biodiversity management. However, the current changing ecological and social conditions have transformed traditional knowledge, and assessment of changes in ethnobotany helps aid conservation of culture and traditional knowledge. Keywords: Plant uses, traditional knowledge, caste/ethnic groups, Tarai origin, buffer zone,